Critical curiosity and lifelong learning: Investigating how mobility programs serve as platforms for intercultural learning and engagement - Trotter, Rachel; McAloney, Kim (Journal of International Students, 2025)
This article examines how higher education institutions can cultivate critical curiosity and foster lifelong learning, thereby creating environments that support ongoing inquiry and both personal and professional growth. It examines the role of global perspectives, inclusive curricula, and experiential learning rooted in lived experiences. The article also considers how mobility programs—such as exchanges, conferences, and collaborative projects—can enhance critical thinking, social awareness, and equitable educational outcomes. By encouraging the participation of students of all backgrounds, these programs serve as platforms for intercultural learning and engagement. Through research and student testimonials, this article analyzes the relationship between critical curiosity and lifelong learning within mobility programs, offering insights into how such initiatives can prepare students to become engaged, socially conscious global citizens. Ultimately, this article highlights how international and global educational opportunities can serve as powerful steppingstones for transformative learning and inclusive academic practices.